Kratom-Induced Cholestatic Liver Injury and Its Conservative Management - Christopher T. Fernandes BS; Umair Iqbal MD; Sean P. Tighe BS; Aijaz Ahmed MD (SAGE Publishing, 2019)
Drug-induced liver injury (DILI) is a common cause of hepatotoxicity associated with prescription-based and over-the-counter exposure to medications and herbal supplements. Use of unapproved and inadequately tested herbal supplements can cause DILI. Therefore, thorough history-taking on exposure to herbal supplements must be an integral part of clinical evaluation of DILI. Kratom is an herbal supplement or remedy that has been known for its analgesic effects and has also been used for self-treatment of opiate withdrawals. A 52-year-old man was seen for evaluation of yellow discoloration of the eyes and skin. He reported taking kratom for right shoulder strain for at least a couple of months. On workup, his total bilirubin was noted to be 23.2 mg/dL, which peaked at 28.9 mg/dL. He was noted to have mild elevation of aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase. Extensive laboratory tests were ordered and known causes of chronic liver disease ruled out. Magnetic resonance imaging of the abdomen was unremarkable without stigmata of portal hypertension or signs of chronic liver disease. He demonstrated no evidence of coagulopathy or hepatic encephalopathy during his illness. He underwent liver biopsy, which demonstrated histologic evidence of acute cholestatic hepatitis highly suspicious of DILI. He was advised to avoid kratom or other herbal supplements in future and prescribed ursodeoxycholic acid with significant improvement in his liver chemistries. Kratom is associated with significant liver enzymes derangements leading to DILI. Kratom is not approved for use in the United States and should be avoided.